Genetic control of the resistance to corn stunt - Silva, Ricardo Gonçalves; Galvão, João Carlos Cardoso; Miranda, Glauco Vieira; Oliveira, Elizabeth de (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to identify the genetic control of the resistance to corn (Zea mays L.) stunt. Two experiments were set up at March 2001, in Coimbra and Sete Lagoas, Minas Gerais State, Brazil. Each experiment consisted of 25 treatments, five of them were represented by maize hybrids. Other treatments were the hybrid combinations and their reciprocal ones. The randomized blocks design with three replicates was used. The experimental plot was integrally used and consisted of two 5 m rows at a 0.9 m spacing from each other, with 25 plants per row, representing a population around 55,000 plants ha-1. At the time of kernel fulfilling, the evaluations were performed for incidence and severity of the corn stunt. The disease index was also used. In both places, the productivity of the maize kernels were evaluated for each plot. Therefore, since this method presents high heritability it was possible to confirm its efficiency. The genetic control of the resistance to corn stunt is mainly controlled by the alleles with predominant addictive effects; the parents differed in relation to the frequency of the addictive and nonaddictive alleles for resistance to corn stunt.